Kewenangan Ombudsman Dalam Penyelesaian Pengaduan Pelayanan Publik - Eufemia Lawati Salabbaet (Darma Cendika Catholic University, 2018)
To prevent maladministration a special institution has been formed to handle maladministration in public services, namely the Ombudsman. The Ombudsman is authorized to process complaints from the public, including adjudication. The authority of the Ombudsman through the adjudication channel becomes a contradiction because the adjudication decision is not final and does not bind the parties, because the adjudication decision has only value as a recommendation. Based on the duties and authorities given to the Ombudsman, the process of resolving complaints of public services by the Ombudsman is the settlement of maladministration reported by the public and settlement of maladministration on its own initiative. The adjudication decision by the Ombudsman also does not provide legal certainty for the parties. Article 1 paragraph (11) of Law No. 25 of 2009 concerning Public Services needs to be changed by placing the adjudication process as the initial litigation process. Then it is necessary to change in Article 1 paragraph (7) of Law No. 37 of 2008 concerning the Ombudsman that the recommendation became one of the points in the dictum of the court's ruling.